Resource partitioning facilitates coexistence in sympatric cetaceans in the California Current. Issue 21 (27th September 2017) - Fossette, Sabrina; Abrahms, Briana; Hazen, Elliott L.; Bograd, Steven J.; Zilliacus, Kelly M.; Calambokidis, John; Burrows, Julia A.; Goldbogen, Jeremy A.; Harvey, James T.; Marinovic, Baldo; Tershy, Bernie; Croll, Donald A.
Abstract: Resource partitioning is an important process driving habitat use and foraging strategies in sympatric species that potentially compete. Differences in foraging behavior are hypothesized to contribute to species coexistence by facilitating resource partitioning, but little is known on the multiple mechanisms for partitioning that may occur simultaneously. Studies are further limited in the marine environment, where the spatial and temporal distribution of resources is highly dynamic and subsequently difficult to quantify. We investigated potential pathways by which foraging behavior may facilitate resource partitioning in two of the largest co‐occurring and closely related species on Earth, blue ( Balaenoptera musculus ) and humpback ( Megaptera novaeangliae ) whales. We integrated multiple long‐term datasets (line‐transect surveys, whale‐watching records, net sampling, stable isotope analysis, and remote‐sensing of oceanographic parameters) to compare the diet, phenology, and distribution of the two species during their foraging periods in the highly productive waters of Monterey Bay, California, USA within the California Current Ecosystem. Our long‐term study reveals that blue and humpback whales likely facilitate sympatry by partitioning their foraging along three axes: trophic, temporal, and spatial. Blue whales were specialists foraging on krill, predictably targeting a seasonal peak in krill abundance, were present in the bay for an average of 4.7 months, and were spatially restricted at the continental shelf break. In contrast, humpback whales were generalists apparently feeding on a mixed diet of krill and fishes depending on relative abundances, were present in the bay for a more extended period (average of 6.6 months), and had a broader spatial distribution at the shelf break and inshore. Ultimately, competition for common resources can lead to behavioral, morphological, and physiological character displacement between sympatric species. Understanding the mechanisms for species coexistence is both fundamental to maintaining biodiverse ecosystems, and provides insight into the evolutionary drivers of morphological differences in closely related species. Abstract : This paper investigates resource partitioning in two of the largest co‐occurring and closely related species on Earth, blue and humpback whales. By integrating long‐term whale surveys, sampling of oceanographic conditions, stable isotope diet analysis, and surveys of prey species we constructed a detailed and comprehensive picture of their differential foraging ecology and resultant resource partitioning. Taken together, our comparisons provide strong evidence of resource partitioning facilitating coexistence, and identify the multiple behavioral mechanisms underlying partitioning.